The influence of metacognition monitoring on L2 Chinese audiovisual reading comprehension - Wang, Yamin; Hu, Jingying; An, Zhuoma; Li, Chaoran; Zhao, Yang (Frontiers in Psychology, 2023)
Metacognition monitoring is the ability to evaluate the cognitive process actively. L2 learners with high metacognition monitoring ability can better monitor reading processes and outcomes consciously, thus facilitating self-regulated learning and improving reading comprehension efficiency. Previous studies mostly used offline self-reports to examine the metacognition monitoring in static text reading by L2 learners. This study investigates the effects of different indicators of metacognition monitoring on L2 Chinese audiovisual comprehension by online confidence judgment and audiovisual comprehension tasks. According to the differences in monitored objects and statistical methods, metacognition monitoring in audiovisual comprehension could be divided into four categories: absolute calibration accuracy based on video or test; relative calibration accuracy measured by Gamma or Spearman correlation coefficient, respectively. 38 intermediate-advanced Chinese learners participated in the study. The results based on multiple regression analysis showed that absolute calibration accuracy can significantly predict L2 Chinese audiovisual comprehension while relative calibration accuracy has no significant effect; the predictive effect of video-based absolute calibration accuracy is affected by the video difficulty, that is, the greater the video difficulty, the greater the impact on the performance of audiovisual comprehension; the predictive effect of test-based absolute calibration accuracy is influenced by the language proficiency, specifically, the higher the L2 Chinese proficiency, the stronger the prediction on the performance of audiovisual comprehension. The findings in this study support a multidimensional view of metacognition monitoring and further clarify the predictive effect of different indicators of metacognition monitoring on L2 Chinese audiovisual comprehension. The article holds that the strategy training of metacognition monitoring should be emphaiszed in practical teaching, and the individual differences between learners and task difficulty should also be fully considered.